NETRALITAS PEJABAT NEGARA DALAM PROSES PEMILIHAN UMUM 2024 - Hapsoro, Fakhris Lutfianto; Sodik, Rozy Brilian (Jurnal Yuridis, 2024)
The neutrality of state officials has one of the benefits of maintaining objectivity in the organisation of the 2024 presidential and vice presidential elections. However, indications of ignoring neutrality clearly appear to be carried out structurally and systematically to maintain the power of the Joko Widodo Government. To find out how the practice of ignoring neutrality is, it is important that this research is carried out using the normative juridical method through the study of Constitutional Court decisions related to the 2024 presidential and vice presidential elections. The results of this study show 4 (four) things, namely first, the conflict of interest of the Chief Justice of the Constitutional Court; Second, the existence of state civil apparatus campaigning; Third, the weak integrity of the election organiser; and Fourth, the abuse of the President's authority.